Comparison of relative INAA and k0-INAA using proficiency test materials at ITU TRIGA Mark II research reactor - Esen, Ayse Nur; Haciyakupoglu, Sevilay; Erenturk, Sema (Springer, 2018)
Proficiency testing is an important way of evaluating the analytical method used in the laboratory. In recent years, neutron activation analysis studies performed in ITU TRIGA Mark II reactor comprised five proficiency tests organized by Wageningen evaluating programs for analytical laboratories. In this study, the results obtained by relative INAA and k (0)-INAA method for 16 elements in soil and plant samples are presented. Since both methods have some advantages compared to each other, the possible approach for the laboratory should be to combine relative INAA and k (0)-INAA results.
7th International K0-Users Workshop -- SEP 03-08, 2017 -- Montreal, CANADA
Keywords: Proficiency Testing; Inaa; Trıga; Soil; Plant; Wepal; Neutron-Activation Analysis